Modeling Role of ICT in Business Startups and Incubation - Pardesi, Gopal (International Journal of Computer Sciences and Engineering, 2025)
Ubiquitous Information Communication Technologies are contributing to further the cause of the startups and incubation process in numerous ways. All starts ups are expected to leverage ICT for understanding the ‘market and cultures’ of various geographies. ICT facilitates the production, transmission, and processing of information. Initial investigation shows that even to work the system (all kind of licenses and permissions from various statutory bodies), ICT driven practices are going to be effective. The paper investigate the areas in which ICT practices can be employed for building efficiencies in the processes of concept to servicing the market. This paper seeks to contribute to the ongoing research in the field of Information & Communication Technology, its impact on the Economic growth & how ICT tools can be used to foster the fast growth of entrepreneurship. Detailed analysis of ICT tools to evaluate the risk capital involved and mitigation of risk in project implementation is done. How modeling and simulation tools be used for projecting the future of a business process is also analyzed. The impact of business analytics/business intelligence techniques for forecasting market behavior is also done thoroughly. Evidence has been collected through a literature search, questionnaires, entrepreneur’s reports and interviews. The detailed study of the challenges faced by startups and the best solutions for them is also done. This paper also analyzes how ICT driven practices & procedures act as a ready reference for Entrepreneurs. This paper also focuses on how ICT plays an important role in fostering innovation leading to enhance firm productivity and economic growth